Business Think and its Relation to the Humility of Department Managers - Al Asadi, Abbas; Al Zaidi, Noor Shaker (Al-Adab Journal, 2018)
The target of current search to know Business Think department managers, recognizing the differences in Business Think according to Gender, Academic achievement, Age, and Specialization. And Humility department managers, recognizing the differences in the Humility according to the same demographic variables. And Correlation between Business Think and Humility. To achieve research goals, we build two scales the first one is Business Think consists (28) items, and Humility consists (26) Items. Verified psychometric properties of the scales above, truly verified reliability coefficient also scales with Cronbach alpha (0.84) for managing Business Think scale, while reliability coefficient of Cronbach Alpha Humility scale (0.78). After application of a sample of measurements (338) member of department managers drawn from the research community, (222) male and (116) female of (Ministry of Labor, and Social Affairs, Ministry of Health and the Environment, Ministry of Industry and Minerals, Ministry of Education, Ministry of Higher Education and Scientific Research, and Ministry of Culture and Tourism and Antiquities) and the current search results have been analyzed in the light of the theoretical framework adopted, contained a number of conclusions, including that section managers management Business Think and there is no interaction between demographic variables in administrative and Business Think that department managers have Humility. There is a difference in the demographic variable Sex in humility and for females and there is no interaction between demographic variables in Humility and there is a positive correlation between Business Think and modesty and management researcher emerged a set of recommendations and proposals.